Volume 1: Processing 2016
DOI: 10.1115/msec2016-8793
|View full text |Cite
|
Sign up to set email alerts
|

Part Damage due to Proximity Effects During Sub-Micron Additive Manufacturing via Two-Photon Lithography

Abstract: Two-photon lithography is a direct laser write process that enables fabrication of millimeter scale 3D structures with nanoscale building blocks. In this technique, writing is achieved via a nonlinear two-photon absorption process during which two photons are near-simultaneously absorbed at high laser intensities. Due to the high laser intensities, it is essential to carefully select the incident power so that two-photon polymerization (TPP) occurs without any laser damage of the resist. Currently, the feasibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…This is because these parameters themselves depend on the writing speed. For example, in our previous empirical work, we have observed that the damage threshold power for single widely spaced lines scales as the 0.47 exponent of the writing speed [19], whereas here we have empirically observed a scaling of 0.21 (Fig. 4).…”
Section: Processcontrasting
confidence: 57%
“…This is because these parameters themselves depend on the writing speed. For example, in our previous empirical work, we have observed that the damage threshold power for single widely spaced lines scales as the 0.47 exponent of the writing speed [19], whereas here we have empirically observed a scaling of 0.21 (Fig. 4).…”
Section: Processcontrasting
confidence: 57%